The effects of positive psychology theory in the rehabilitation nursing of Chinese patients with schizophrenia: a systematic review and meta-analysis of randomized controlled trials - Yu Hong; Yanjun Huang; Junhong Jiang; Qiuhua Liu; Jing Hu; Wenfei Tan; Jinying Deng; Xintian Wang (Frontiers in Psychiatry)
BackgroundSchizophrenia is a complex and severe chronic mental disorder characterized by persistent cognitive dysfunction. Particularly in Chinese families, the disability of patients with schizophrenia and the burden on their caregivers are especially heavy, reflecting the profound impact of the disease on both the patients and their families. Positive psychology is a science that focuses on human happiness, strengths, and potential. It originated at the end of the 20th century, advocated by psychologists such as Martin Seligman, aiming to go beyond the traditional psychology’s focus on diseases and deficiencies and instead explore how to help people achieve the best mental state and quality of life. This study aims to conduct a meta-analysis to evaluate the impact of positive psychology interventions on Chinese patients with schizophrenia.ObjectivesThis study aims to explore the impact of positive psychology on the wellbeing, positive symptoms, negative symptoms, depressive symptoms, social functioning, social adaptability, and cognitive functions of patients with schizophrenia.MethodsLiterature was retrieved from 11 databases (CNKI, Wan fang Database, VIP Database, CBM Database, PubMed, EMBASE, Cochrane Library, Web of Science, APA PsycINFO, CINAHL, and MEDLINE), with the search period ranging from the inception date to 1 August 2024. Two researchers independently conducted literature reviews, data extraction, and bias risk assessments. The quality of the included studies was assessed using the Cochrane Risk of Bias tool, and meta-analyses were conducted using RevMan 5.3 and Stata 14.0. The continuous outcomes were analyzed by calculating the mean difference (MD) or standardized mean difference (SMD) with 95% confidence intervals (CI) according to whether combining outcomes measured on different scales or not, depending on whether the results measured by different scales were combined.ResultsA total of 54 randomized controlled trials met the criteria for this study. The results showed that positive psychology can significantly improve the wellbeing of Chinese patients with schizophrenia (MD = 0.61, 95% CI = 0.56 to 0.66, p < 0.001, I2 = 0%), and long-term and mid-term treatments were significantly better than short-term treatments (p < 0.001). Positive psychology can significantly improve the psychological health status of Chinese patients with schizophrenia (MD = 43.50, 95% CI = 40.11 to 46.89, p < 0.001, I2 = 0%), and long-term and mid-term treatments were significantly better than short-term treatments (p = 0.004). Positive psychology can significantly improve the positive symptoms of Chinese patients with schizophrenia (SMD = −2.68, 95% CI = −3.53 to −1.84, p <0.001, I2 = 95%), and long-term and mid-term treatments were significantly better than short-term treatments (p < 0.001). Positive psychology can significantly improve the negative symptoms of Chinese patients with schizophrenia (SMD = −2.63, 95% CI = −3.40 to −1.87, p < 0.001, I2 = 94%), and long-term and mid-term treatments were significantly better than short-term treatments (p < 0.001). Positive psychology can significantly improve the social functioning of Chinese patients with schizophrenia (MD = −2.68, 95% CI = −3.26 to −2.10, p < 0.001, I2 = 94%), and long-term and mid-term treatments were significantly better than short-term treatments (p < 0.001). Positive psychology can significantly improve the self-esteem of Chinese patients with schizophrenia (MD = 7.98, 95% CI = −7.53 to 8.42, p < 0.001, I² = 0%). Positive psychology can significantly improve the social adaptability of Chinese patients with schizophrenia (MD = −8.72, 95% CI = −9.16 to −8.27, p < 0.001, I² = 0%). Positive psychology can significantly improve the cognitive function of Chinese patients with schizophrenia (MD = 2.38, 95% CI = 1.97 to 2.78, p < 0.001, I2 = 38%).ConclusionPositive psychology has significant effects on enhancing the wellbeing of Chinese patients with schizophrenia. It not only improves the positive and negative symptoms of the disorder but also strengthens social adaptability and cognitive functions. Moreover, positive psychology provides clear benefits in alleviating depressive symptoms among individuals with schizophrenia. Notably, the long-term adherence to positive psychological interventions yields much better treatment outcomes than short-term interventions. Therefore, we recommend the widespread application of positive psychology in clinical treatment.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024585178.